A compact high-frequency link inverter for UPS application - Salam, Z.; Ayob, S. M.; Toh, L. S. (Praise Worthy Prize, 2006)
This paper presents the design of a compact and lightweight bidirectional high-frequency link inverter that can be suitably used for uninterruptible power supplies (UPS). The electrical isolation between the mains and the load is provided by a centre-tapped high-frequency transformer. The inverter is controlled by a Deadbeat controller, which consists of inner current loop, outer voltage loop and a feedforward controller. A 1 kVA prototype inverter has been designed and constructed. The experimental results show that the inverter has high efficiency (91%) with low output voltage distortion (THD less than 1.5%)